2021
DOI: 10.4103/2096-2924.309789
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Preservation in Cancer Patients

Abstract: Traditional radiotherapy and chemotherapy often cause irreversible damage to the fertility and endocrine function of cancer patients. The current methods of fertility preservation include freezing the sperms of adult and adolescent males after puberty; freezing the embryos, oocytes, and ovarian tissue of females; and drug intervention and fertility preservation surgery. This article reviews fertility preservation in cancer patients with respect to current methods, indications, and some more recently developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…(2) Organizational level The organizational context also has an important impact on mindfulness. Reb et al (2015) showed that the organizational physical environment and organizational feedback are predictive of employee mindfulness, where organizational constraints negatively predicts employee mindfulness and organizational support positively predicts employee mindfulness [35] ; Zhang Jing et al (2017) believe that the simple and beautiful design style of the workplace is conducive to reducing interference factors affecting mindfulness, thus improving employee mindfulness [36] .…”
Section: Mindfulness Served As the Outcome Variablementioning
confidence: 99%
“…(2) Organizational level The organizational context also has an important impact on mindfulness. Reb et al (2015) showed that the organizational physical environment and organizational feedback are predictive of employee mindfulness, where organizational constraints negatively predicts employee mindfulness and organizational support positively predicts employee mindfulness [35] ; Zhang Jing et al (2017) believe that the simple and beautiful design style of the workplace is conducive to reducing interference factors affecting mindfulness, thus improving employee mindfulness [36] .…”
Section: Mindfulness Served As the Outcome Variablementioning
confidence: 99%
“…FP methods include ovarian transposition, oocyte or embryo cryopreservation, and ovarian tissue cryopreservation (OTC) (Anbari et al, 2022). OTC is the only pre-treatment option currently available for FP in prepubescent and adult females who cannot undergo ovarian stimulation or a delay in oncological therapy (Handling et al, 2021;Herraiz and Cervello, 2020;Jing et al, 2021;Margita et al, 2022; International Society for Fertility Preservation-ESHRE-ASRM Expert Working Group, 2017; Practice Committee of American Society for Reproductive Medicine, 2014). Meanwhile, OTC can restore the reproduction function.…”
mentioning
confidence: 99%